2013
DOI: 10.1128/aem.00846-13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli O157:H7 Strains Isolated from Supershedding Cattle

Abstract: Previous reports have indicated that a small proportion of cattle shedding high levels of Escherichia coli O157:H7 is the main source for transmission of this organism between animals. Cattle achieving a fecal shedding status of 10 4 CFU of E. coli O157: H7/gram or greater are now referred to as supershedders. The aim of this study was to investigate the contribution of E. coli O157:H7 strain type to supershedding and to determine if supershedding was restricted to a specific set of E. coli O157:H7 strains. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 54 publications
5
60
0
Order By: Relevance
“…In addition, all SS-O157 and control O157 strains adhered to HEp-2 cells in a "diffuse and moderate" pattern (Table 1). An initial screening on CRI plates confirmed that the control strains were curli-expressing (C ϩ ) strains as reported in other studies (27), but the SS-O157 strains differed in their levels of curli production, with only strains SS-12 and SS-42 appearing to be C ϩ (34,35). Since neither the RSE cell adherence patterns nor the HEp-2 cell adherence patterns of these O157 strains could be associated with their respective curli phenotype (Table 1), it appeared that, in contrast to previous reports (25)(26)(27)29), the adherence was not dependent on the curli fimbriae.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, all SS-O157 and control O157 strains adhered to HEp-2 cells in a "diffuse and moderate" pattern (Table 1). An initial screening on CRI plates confirmed that the control strains were curli-expressing (C ϩ ) strains as reported in other studies (27), but the SS-O157 strains differed in their levels of curli production, with only strains SS-12 and SS-42 appearing to be C ϩ (34,35). Since neither the RSE cell adherence patterns nor the HEp-2 cell adherence patterns of these O157 strains could be associated with their respective curli phenotype (Table 1), it appeared that, in contrast to previous reports (25)(26)(27)29), the adherence was not dependent on the curli fimbriae.…”
mentioning
confidence: 76%
“…Eight previously characterized O157 isolates obtained from supershedding cattle were used in this study (34,35). These supershed (SS) O157 isolates included SS-7, SS-12, SS-17, SS-27, SS-42, SS-52, SS-67, and SS-77 (Table 1) (34,35).…”
Section: Bacterial Strains (I) O157 Wild-type Isolatesmentioning
confidence: 99%
“…Further, the discovery of cattle reservoirs shedding high levels of STEC O157: H7, which has been associated with the transmission between animals and across the human-animal interface (30,31), strongly supports the idea that adoption of vaccination for livestock and/or susceptible individuals will have significant public health benefits, preventing substantial numbers of human STEC O157 cases (32). Therefore, further discovery for EHEC-specific antigens needs to be done to improve existing or to develop novel vaccines.…”
mentioning
confidence: 99%
“…It can be speculated that this would provide a large concentration and volume of strain-specific contamination that would need to be reduced through proper dressing and functional interventions. However, this scenario seems unlikely, because supershedders make up approximately 2% of the cattle population (26), and multiple supershedders likely enter processing plants on a daily basis during high shedding season. As shown in Tables 2 and 3, there is little evidence of incoming cattle hides being contaminated with predominantly one strain type.…”
Section: Discussionmentioning
confidence: 99%
“…The FSIS isolates had a similar high rate (81.3%) of human illness-associated strain types, indicating that the tir T allele may not be associated specifically with HEP but rather with beef trim in general. It should be noted that the tir T allele was recently found to have a prevalence of 71% among E. coli O157:H7 strains isolated from supershedding cattle (26). More data will be needed to determine if human illnessassociated strains are associated with beef trim and if supershedding plays a role in such an association.…”
Section: Discussionmentioning
confidence: 99%